Changing Roles of Librarians And Information Professionals In A Knowledge-Based Society - Ng, Judy (2015)
In a digital and knowledge based environment, library professionals have to change from one that is traditionally as just an information provider to that of knowledge provider. In information provision, the library professional provides "explicit" knowledge in the form of book, journals, reports, etc. In knowledge provision, the library professionals provide intellectual output that involves analysis and evaluation of the information provided. New technologies also provide new opportunities and ways in which library professionals can deliver their services. This paper discusses the challenges of the global digital environment and the shift in the roles of the library professionals.